Pengaruh Kepuasan Kerja Terhadap Organizational Citizenship Behavior (Ocb) Di RS Stella Maris Makassar - Mira Gusweni (Puslatbang KHAN, 2017)
Organizational Citizenship Behavior (OCB) is the behavior of the freedom of determining which is not part of the formal job requirements of workers, but contributes to the psychological and social environment workplace. The aim of the research was to determine the effect of job satisfaction on organizational citizenship behavior (OCB) in Stella Maris Hospital of Makassar in 2015. The research was quantitative with analytic study and using survey method. The number of sample is 161 people. The determination of the sample size was done in total sampling. Data collection was done through observation, questionnaire, and documentation. Data were analyzed univariat, bivariate with chi square test. The results showed that job satisfaction has significant effect on organizational citizenship behavior with statistical test result (p=0.000).